AKTIVITAS FISIK DAN PENINGKATAN BASAL METABOLISME RATE PADA PASIEN DIABETES MELITUS - Anggita, Dini; Fauzan, Suhaimi; Neri, Ervina Lili; Maulana, Muhammad Ali; Murtilita, Murtilita (Jurnal Keperawatan dan Kesehatan, 2024)
Diabetes mellitus basically occurs due to insulin intolerance which causes high blood glucose and if not controlled can cause complications and even death. One of the efforts to overcome Diabetes Mellitus is to change lifestyle by increasing physical activity. This study aimed to determine the relationship between physical activity and an increase in basal metabolic rate in diabetes mellitus patients in the working area of UPT Puskesmas Perumnas 2. This research was quantitative research with cross-sectional. Using the Pearson correlation test. Basal Metabolism Rate is measured using formula provisions and physical activity scores using the GPAQ questionnaire sheet. with a total of 100 respondents obtained using a purposive sampling technique. The research results showed Hypothesis testing uses the Pearson correlation statistical test with a p-value of 0.000 which was less than <0.05, so it can be concluded that Ho is rejected, meaning that there is a relationship between physical activity and an increase in basal metabolic rate in diabetes mellitus patients. This research shows that there is a relationship between physical activity and an increase in basal metabolic rate in diabetes mellitus patients in the working area of the UPT Puskesmas Perumnas 2.